Oral administration of melatonin modulates the expression of tumor necrosis factor-α (TNF-α) gene in irradiated rat cervical spinal cord - Haddadi, Gholam Hassan (Rep Pract Oncol Radiother, 2015)
AIM: We aimed to determine the changes in TNF-α expression and Malondialdehyde (MDA) level in a short time after irradiation. Furthermore, we evaluated the effect of melatonin on the modulation of TNF-α gene expression. BACKGROUND: The radio-sensitivity of the cervical spinal cord limits the dose of radiation which can be delivered to tumors in the neck region. There is increasing evidence that TNF-α has a role in the development of the acute phase of spinal cord injury. MATERIALS/METHODS: Four groups of rats were investigated. Group 1 (vehicle treatment) served as the control. Group 2 (radiation) was treated with the vehicle, and 30 min later, the rats were exposed to radiation. Group 3 (radiation + melatonin) was given an oral administration of melatonin (100 mg/kg body weight) and 30 min later exposed to radiation in the same manner as in group 2. Group 4 (melatonin-only) was also given an oral administration of melatonin (100 mg/kg body weight). 5 mg/kg of melatonin was administered daily to rats in groups 3 and 4, and the vehicle was administered daily to rats in groups 1 and 2. RESULTS: Three weeks after irradiation, TNF-α gene up-regulated almost 5 fold in the irradiated group compared to the normal group. TNF-α gene expression in the melatonin pretreatment group, compared to the radiation group, was significantly down-regulated 3 weeks after irradiation (p < 0.05). MDA levels increased after irradiation and then significantly decreased under melatonin treatment. CONCLUSION: We suggest that inhibition of TNF-α expression by oral administration of melatonin may be a therapeutic option for preventing radiation-induced spinal cord injury.